2022
DOI: 10.1111/plb.13406
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide‐mediated alleviation and its interplay with other signalling molecules during temperature stress

Abstract: The sessile habit of plants does not provide choices to escape the environmental constraints, leading to negative impacts on their growth and development. This causes significant losses in the agriculture sector and raises serious issues on global food security. Extreme temperatures (high or low) influence several aspects of plant life and can cause reproduction malfunction. Therefore, a strategy for temperature amelioration is necessary for the management of agricultural productivity. Supplementation with var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…Unfortunately, both potassium and imidazolium salts of D and F were insoluble in these solvents. Moreover, hydrolysis of compound D in 90% H 2 O/D 2 O was investigated at 85 °C and room temperature by 31 P NMR spectroscopy. After 30 days, only 18% hydrolyzed at 85 °C and less than 3% hydrolyzed at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, both potassium and imidazolium salts of D and F were insoluble in these solvents. Moreover, hydrolysis of compound D in 90% H 2 O/D 2 O was investigated at 85 °C and room temperature by 31 P NMR spectroscopy. After 30 days, only 18% hydrolyzed at 85 °C and less than 3% hydrolyzed at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S) is a key gasotransmitter in plants that affects numerous enzymatic pathways within, and between cells, and the addition of exogenous H 2 S often has a strong positive effect at surprisingly low doses on maize, soybean, wheat, cucumber, peas, tomatoes, broccoli, lettuce, sugar beets, strawberries, radishes, and kiwi plants. , H 2 S is produced in cells and found at nanomolar concentrations, and recent work has shown that applying exogenous H 2 S to plants has dramatic effects, including increasing their overall size and mass, protection from high salt concentrations, protection from heat and drought stress, increased root growth, and prolonged shelf life of harvested crops. ,,, For example, the addition of exogenous H 2 S to plants such as over a dozen different plants increases their ability to withstand salt stress. , Although the process by which exogenous H 2 S enables plants to survive salt stress is complex, it has been shown to increase the activity of antioxidant enzymes, affect the levels of Na + in cells, and regulate several signaling proteins. The importance of exogenous H 2 S in agriculture has been established, and many current studies investigate the fundamental biochemistry of H 2 S within plants and how to apply H 2 S in a safe, dependable manner . Most of the early work in this field used micro to millimolar concentrations of aqueous H 2 S delivered once or twice daily.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other abiotic stresses, extreme temperatures (heat and cold) affect plant growth and development and trigger the biosynthesis of H 2 S, which regulates physiological, biochemical and molecular mechanisms, resulting in better growth under several environmental stresses. Mishra et al (2022) provide an assessment and comprehensive review of H 2 S-mediated extreme temperature stress mitigation and addresses effective mitigation strategies to manage heat and cold stresses. Waterlogging is detrimental to plants and impairs the yield of legume crops that are sensitive to submergence.…”
Section: Emerging Role Of Hydrogen Sulphide As a Signalling Molecule ...mentioning
confidence: 99%
“…Mishra et al . (2022) provide an assessment and comprehensive review of H 2 S‐mediated extreme temperature stress mitigation and addresses effective mitigation strategies to manage heat and cold stresses. Waterlogging is detrimental to plants and impairs the yield of legume crops that are sensitive to submergence.…”
mentioning
confidence: 99%
“…These enzymes and H 2 S have a leading role in numerous physiological processes from seed germination to plant senescence. As mentioned above, H 2 S can not only exert its physiological functions alone ( Li et al., 2016 ; Liu et al., 2021 ) but also regulates the acquirement of stress tolerance including thermotolerance in plants by interacting with NO ( Li et al., 2013 ; Xie et al., 2018 ; Huang et al., 2021 ; Li et al., 2021 ; Gautam et al., 2022a ; Mishra et al., 2022 ; Sehar et al., 2022 ). However, the exact interaction mechanism between H 2 S and NO in plants is not completely clear.…”
Section: Introductionmentioning
confidence: 99%